1996
DOI: 10.1007/bf00019107
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress induces an increased expression of V-type H+-ATPase in mature sugar beet leaves

Abstract: In the halotolerant sugar beet co-expression of V-ATPase and a vacuolar Na+/H(+)-antiporter provides a mechanism for vacuolar salt sequestration. To analyze salt-induced changes in the expression of the vacuolar H(+)-ATPase (V-ATPase) a partial cDNA of the proton-channel forming subunit c was cloned by RT-PCR. Southern blot analysis indicated a small gene family. In control plants transcript levels were high in roots and young growing leaves but low in fully expanded leaves. In mature leaves salt exposure (400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 25 publications
1
35
0
1
Order By: Relevance
“…Thus, it would appear that they are able to compartmentalize Na + in vacuoles in order to adapt to osmotic stress and avoid toxicity. In fact, in spinach a strict compartmentalisation of Na + and Clin the vacuole has been demonstrated (Coughlan and Wyn Jones 1980), and in sugar beet leaves saline stress induced a marked activation of the V-ATPase, increasing the proton-motive force that is used by Na + /H + antiports through the tonoplast (Kirsch et al 1996). Our results with beetroot coincide with those from sugar beet, which indicate that established plants showed high osmotic adjustment and accumulation of gycinebetaine, proline and inorganic ions (Na + , K + and Cl -) under saline stress (Heuer and Plaut 1989;Gzik 1996;Ghoulam et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it would appear that they are able to compartmentalize Na + in vacuoles in order to adapt to osmotic stress and avoid toxicity. In fact, in spinach a strict compartmentalisation of Na + and Clin the vacuole has been demonstrated (Coughlan and Wyn Jones 1980), and in sugar beet leaves saline stress induced a marked activation of the V-ATPase, increasing the proton-motive force that is used by Na + /H + antiports through the tonoplast (Kirsch et al 1996). Our results with beetroot coincide with those from sugar beet, which indicate that established plants showed high osmotic adjustment and accumulation of gycinebetaine, proline and inorganic ions (Na + , K + and Cl -) under saline stress (Heuer and Plaut 1989;Gzik 1996;Ghoulam et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, previous work suggested that vacuolar sodium accumulation in salt-tolerant plants may be mediated by a tonoplast Na ϩ ͞H ϩ antiporter that utilizes the protonmotive force generated by the vacuolar H ϩ -ATPase (VATPase) and͞or H ϩ -translocating pyrophosphatase (VPPase; refs. [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been shown that NaCl but not ABA can stimulate V-ATPase activity (20). Salt-induced transcript up-regulation of one or more V-ATPase subunits or an increase in V-ATPase activity has also been observed in a number of glycophytic species (3,4,22,30,45,61). This includes A. thaliana, where an increase in the transcript levels of AtVHA-C (36) but not of subunit D (AtVHA-D) (23) was found upon salt stress.…”
mentioning
confidence: 93%